Response to Rachelle Green's Keynote Address: ‘Just Mercy: Theo-Ethical Reflections for Practicing Care in Carceral and Other Death-Dealing Spaces’ - Moschella, Mary Clark (Journal of pastoral theology, 2025)
This article begins with a poetic response to Rachelle Green's keynote presentation, which has evoked a picture of mercy and no-mercy in the context of carceral life. The author notes with appreciation the importance of the keynote address to the field of pastoral theology. Finally, the author asks the presenter three questions for further amplification and discussion.